The Impact of Psychological Empowerment on Individual Performance in Balloon Companies: Is Justice Perception a Mediator? - Yilmaz, Rabia (Journal of Ecohumanism, 2024)
Today’s organizations inevitably experience rapid changes at every moment. One factor that plays an important role in the success of organizations in this change is their employees. This study aims to examine the intermediary role of justice in the impact of psychological empowerment perceptions of employees working in balloon businesses belonging to the private aviation industry on individual performance. The study used a convenience sampling method, and the data were obtained from 454 employees by questionnaire. The study used the SPSS 25.0 Program and Process Macro v 4.0 application. Frequency analysis, exploratory factor analysis, confirmatory factor analysis, and reliability analysis were conducted. In addition, descriptive statistics, correlation analysis, regression, and mediating effects were analyzed using the bootstrap method developed by Hayes (2013). In addition, the Sobel test was used to examine the significance of the mediating effect. As a result of the study, the relationship between competence and interactional justice (r =.550; p =.000) is higher than other variables. Moreover, psychological empowerment has a significant and positive impact on individual performance (95% CI [.37; .59]; ß=.4553; p=.000). In addition, psychological empowerment has a significant and positive impact on the justice perception (95% CI [.31; .32]; ß=0.191; p=.000). Justice perception has a significant and positive impact on individual performance (95% CI [.32; .47]; ß=.4052; p=.000). Finally, justice perception has a semi-intermediary impact on psychological empowerment and individual performance (ß=.7892) and (95% CI [.1431, .1488]).